Anterior Lumbar Interbody Fusion as a Salvage Technique for Pseudarthrosis following Posterior Lumbar Fusion Surgery. (February 2016) - Mobbs, Ralph J.; Phan, Kevin; Thayaparan, Ganesha K.; Rao, Prashanth J.
Study Design: Retrospective analysis of prospectively collected observational data. Objective: To assess the safety and efficacy of anterior lumbar interbody fusion (ALIF) as a salvage option for lumbar pseudarthrosis following failed posterior lumbar fusion surgery. Methods: From 2009 to 2013, patient outcome data was collected prospectively over 5 years from 327 patients undergoing ALIF performed by a single surgeon (R.J.M.) with 478 levels performed. Among these, there were 20 cases of failed prior posterior fusion that subsequently underwent ALIF. Visual analog score (VAS), Oswestry Disability Index (ODI), and Short Form 12-item health survey (SF-12) were measured pre- and postoperatively. The verification of fusion was determined by utilizing a fine-cut computed tomography scan at 12-month follow-up. Results: There was a significant difference between the preoperative (7.25 ± 0.8) and postoperative (3.1 ± 2.1) VAS scores ( p < 0.0001). The ODI scale also demonstrated a statistically significant reduction from preoperative (56.3 ± 16.5) and postoperative (30.4 ± 19.3) scores ( p < 0.0001). The SF-12 scores were significantly improved after ALIF salvage surgery: Physical Health Composite Score (32.18 ± 5.5 versus 41.07 ± 9.67, p = 0.0003) and Mental Health Composite Score (36.62 ± 12.25 versus 50.89 ± 10.86, p = 0.0001). Overall, 19 patients (95%) achieved successful fusion. Conclusions: Overall, our results suggest that the ALIF procedure results not only in radiographic improvements in bony fusion but in significant improvements in the patient's physical and mental experience of pain secondary to lumbar pseudarthrosis. Future multicenter registry studies and randomized controlled trials should be conducted to confirm the long-term benefit of ALIF as a salvage option for failed posterior lumbar fusion.